Study of microwave-assisted extraction of polyphenol from Phyllanthus urinaria - Ngo, Dat Trinh Tac; Tran, Ngoc Hieu; Hoang, Kim Anh (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: Phyllanthus urinaria, found extensively in tropical Asian countries, possesses numerous biological activities attributed to its polyphenol compounds.Objective: This study aims to optimize polyphenol extraction from Phyllanthus urinaria using microwave assistance.Materials and Methods: First, the effects of parameters including ethanol concentration (used as the solvent) (40–80% v/v), material-to-solvent ratio (1:10–1:50 w/v), extraction time (30–150 minutes), and extraction temperature (30–70°C) on conventional extraction were investigated. Subsequently, the effects of microwave pretreatment prior to extraction during the microwave-assisted extraction (MAE) process, including microwave power (100–700 W) and irradiation time (1–9 minutes), were evaluated. Optimal extraction conditions were determined based on total flavonoid content (TFC), total phenolic content (TPC), and antioxidant activity (DPPH scavenging assay) of the extract. The second-order kinetic model was also used to compare the efficiency of extraction methods.Results: Results indicated that a microwave power of 250 W and irradiation time of 3 minutes were optimal for material pretreatment prior to extraction. Subsequent extraction parameters included ethanol concentration of 60% (v/v), solvent-to-material ratio of 1:40 (w/v), extraction temperature of 50°C, and extraction time of 60 minutes. Under these conditions, the extract exhibited maximum levels of TPC (277.99 ± 5.47 mgGAE/gDW), TFC (38.90 ± 0.58 gQE/gDW), and TEAC (280.08 ± 0.75 µmolTE/gDW), which were 22.5%, 36.1%, and 29.4% higher, respectively, compared to the control without microwave treatment.Conclusion: Furthermore, the second-order kinetic model demonstrated higher initial extraction rate (h), extraction rate constant (k), and extraction capacity (Ce) for MAE compared to conventional extraction.Keywords: Antioxidant capacity; kinetic model; microwave-assisted extractio; phyllanthus urinaria; polyphenol